ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI SAWAH di Kecamatan Sipora Utara Kabupaten Kepulauan Mentawai Tahun 2011 - , Yusufhadisumarto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study on the analysis of the factors affecting rice farmers' income Sipora case study of the northern districts Mentawai Islands regency, 2011. Necessary data in this study were primary and secondary data. Primary data obtained through interviews with rice farmers in the district of North Sipora Mentawai Islands District with a list of questions that have been provided. Secondary data was collected from various sources ie offices / agencies. Analysis tool that is used to determine the factors affecting rice farmers' income is the multiple linear regression. Dependent variable is the production of rice, while the independent variable is the land area, number of seeds, labor, fertilizer and pesticides, to know the average income per hectare of land of farmers using a cost function analysis, to determine the factors affecting rice farmers' income used the linear regression Simple. Dependent variable is income, while the independent variable is the production. Subsequently analyzed by the method of Ordinary Least Square (OLS). From the analysis of the factors that affect rice production is obtained that the area of land, seed, labor, fertilizer and pesticides is jointly significant effect (significant) on rice production. That the use of production factors TK and PPK show positive and significant effect on rice production, while the use of production factors PSTD and BBT showed no significant effect. These factors together showed a significant effect on rice production. Average land to expand production at one time the season was 3333.36 kg / ha. Results of data analysis, it is known that the average revenue yield paddy farming Rp15.015.750,00 / ha less variable costs once the season is Rp8.047.650,93 / ha, the net income of rice farmers on a one-time production / planting rice at Rp6.968.099,07 / ha. The results of data analysis the influence of productivity on net income showed a positive and significant impact on net income of rice farmers.